Penggunaan Alat Pengatur Konsentrasi Kaporit (Ca(ClO)2) dalam Meningkatkan Efektifitas Desinfeksi Peralatan Makan - Siti Noor A’in A’fifah Puteri; Rahmawati Rahmawati; Darmiah Darmiah (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2017)
Abstract: The Use Of Chlorine Concentration Controller (Ca(ClO)2) In Improving The Effectiveness Of Cutlery Disinfection. About 80% of food-cause disease and food poisoning are caused by microbial contamination, one of which comes from the equipment used. Equipment potential as food contamination is not clean enough and not appropriate washing process, because it skips over disinfection stage. One of cutlery disinfection process is by giving active chlor (chlorine) at concentration 50 ppm. This study aimed to determine the ability of the use of chlorine concentration controller (Ca(ClO)2) in improving the effectiveness of cutlery disinfection. This study used experimental method, the data was obtained by trial the accurate chlorine concentration (Ca(ClO)2), plate samples immersed using chlorine solution and laboratory test of number bacteria and E.coli parameters. The results of chlorine (Ca(ClO)2) concentration controller were confirmed that in one press the apparatus could removable solution of 2 mL equivalent to 50 ppm if it used for 1 L of water. Based on the result of laboratory examination was known that the number of germs post-treatment was smaller than pre-treatment and negative E.coli on pre and post-treatment. The contact time determined the percentage decrease of germs after disinfection. The contact time at 2 minutes could reduce the number of germs of 99,08%. Keywords : Chlorine (Ca(ClO)2); Disinfection